NONLIN: A New Version for Simplified Use in BASIC Computer Systems - Meystre, A.; Leishman, B.; Eckert, M. (Methods of Information in Medicine, 1982)
A translation of the well-established program NONLIN into the BASIC language is presented. This modified (simplified) version can be used by clinicians and others interested in pharmacokinetics without extra assistance.The models are programmed in the same way as the DFUNC subroutines of the FORTRAN version. The most widely used pharmacokinetic models are stored as a small library and are accessible under their names.
Keywords: NONLIN; BASIC; Pharmacokinetics